Dokąd zmierza historia w Afryce? - Adeboye, Olufunke (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2024)
Translation of the opening lecture during XXIII International Congress of Historical Sciences (WHERE IS HISTORY GOING IN AFRICA?)